Use of Istijrar Contract as Financing Model for Islamic Banks in Türkiye - Gürler, Safiye Sena Baytan; Kayadibi, Saim (Journal of Islamic Economics and Finance Studies, 2025)
This research examines the istijrar contract as a potential solution to the operational and Shariah compliance challenges commonly encountered in murabahah-based financing, particularly in scenarios involving continuous and repeated purchases. Such flexible purchasing arrangements often generate complexities and elevate compliance risks. To address these issues, the study adopts a structured literature review methodology, implemented in three stages. First, it reviews scholarly debates concerning the Shariah compliance of the istijrar contract. Second, it assesses existing global practices. Third, it analyzes Turkish practices and legal regulations, critically examining the discussions and models at each stage to identify the most suitable adaptation for implementation in Türkiye. Key findings highlight the absence of standardized frameworks in both global and Turkish contexts, along with the limited practical application of istijrar in Türkiye’s Islamic banking sector. In response, this research synthesizes these insights to develop a structured and independent istijrar model specifically tailored to the Turkish Islamic banking environment. It is anticipated that this model will enable Islamic banks to more effectively finance customers engaged in production and trade activities, thereby supporting the growth of the real economy.